Early school adjustment: Do social integration and persistence mediate the effects of school-entry skills on later achievement?. (February 2021) - Schmerse, Daniel; Zitzmann, Steffen
Abstract: The present study sought to determine the relative contributions of two aspects of school adjustment to children's academic progress. We asked if social integration and persistence of effort mediate effects of preschool academic skills, peer problems, and disruptive behavior on Grade 4 achievement. Results based on a German sample of children from preschool to Grade 4 (N = 526) indicated that persistence of effort in Grade 1 but not social integration predicted later achievement. Preschool disruptive behaviors were associated with lower levels of persistence. Peer problems negatively predicted social integration. Results showed further that students who entered school with stronger math skills were more likely to persist in academic tasks and to be socially well-integrated. Persistence mediated the total effect of preschool math skills on both Grade 4 math (22%) and reading (54%) achievement. The findings substantiate the mediating role of persistence on academic trajectories over the elementary years. Highlights: Preschool peer problems negatively predicted social integration in Grade 1. Preschool math skills were associated with persistence of effort in Grade 1. Persistence but not social integration in Grade 1 predicted later achievement. Persistence mediated 54% of preschool math skills on Grade 4 reading.